IDEOLOGICAL CONTESTATION ON YOUTUBE BETWEEN SALAFI AND NAHDHATUL ‘ULAMA IN INDONESIA - Nur'aeni, Ulvah; Ramdan, Arfian Hikmat (UIN Sumatera Utara, 2023)
Abstract: This research spotlights YouTube’s utilization as a platform for intriguing Muslims and proselytizing Salafi and Nahdhatul 'Ulama's (NU) doctrines in the context of ideological contestation in Indonesia. This aim was motivated by the struggle for religious authority between NU and Salafis that has occurred in Indonesia since the beginning of the emergence of Salafis in the 1970s. The doctrine of Puritanism brought by Salafis is the key to the ideological battle with NU, which has the opposite doctrine. Thus, the contestation spread to the fight for the masses. One medium used as an object for spreading doctrine is YouTube. This use of YouTube is encouraged by their awareness that YouTube is an effective platform for proselytizing and arguing with each other. Therefore, this research explores the ideological contestation of the two groups from the aspect of the doctrine they spread and the ways they attract the masses by analyzing lecture videos from YouTube channels affiliated with each group. Based on the content and video quantity, this research argues that the massive method of being charged with Salafis is slowly becoming a strong challenge for the existence of NU. The method used is a theory by Heidi A. Campbell regarding online authority.Keywords: Ideological Contestation, Nahdhatul ‘Ulama, Religious Authority, Salafi, YouTube.